TWO-DIMENSIONAL THEORETICAL MODEL DEVELOPMENT OF DESICCATION CRACK FORMATION ON DISTURBED CLAYSHALE - Noor Rachma, Saraswati
Desiccation cracks phenomenon commonly occurs. The existence of drying and wetting process causes changes in soil water content, resulting inhomogeneous of swelling and shrinkage soil. The process causes stress on the soil so that the cracks will be formed. This presence of cracks will cause inhomogeneous soil water content in certain areas, so that seepage flow will be occurred. The presence of water flow in soil may be causing a new soil failure plane. Cracks network is randomly formed and the methods for predicting crack network are still not much developed. Thus, a desiccation test was carried out to determine the simple theory of two-dimensional crack network in disturbed clay shale soils. The test is conducted in a laboratory by using two different tray geometries: square and circular. The dimension of each tray is 100 cm length and 2 cm height. The soil used in this experiment was taken from Cisomang area and was mixed with water to form slurry soil. The obtained results from the tests are soil shrinkage curves, visual observations of crack propagation, and a theory to predict two-dimensional crack network in desiccated soil. Based on the soil shrinkage curve, the volumetric water content in the test soil has a value of 0.85. For the results of the crack propagation that formed in the both trays give a similar pattern tendency, so that the theory can be drawn the formation of soil crack network with certain boundaries described in this paper.